The fat firm the transformation of a firm from fat to fit - Zoltners, Andris A. (McGraw-Hill, 1997)
Yes, you can laugh your way to a better-running, leaner business. The Fat Firm proves it. Combining the talents of serious business, management, marketing, and learning experts--and one dynamite cartoonist--this book brings you unforgettably funny lessons on the ways real companies work. Destined to be photocopied and posted on office bulletin boards everywhere, the cartoons in this book point up home truths on company politics, practices, and processes. Better yet, the sardine-factory-running sea lions in The Fat Firm show you there's a superior way! The Fat Firm is serious fun for everyone who cares about the place they work.